2015
DOI: 10.4028/www.scientific.net/msf.820.218
|View full text |Cite
|
Sign up to set email alerts
|

Curvature Evolution of Porcelain Tile during Firing

Abstract: Planarity is one of indispensable attribute of a ceramic tile quality. During the firing changes on curvature may be permanent causing damage on quality and productivity. The objective was to evaluate curvature evolution on porcelain tile during heating stage of firing. Effects of engobe and glaze coating were evaluated. The performance of two compositions of porcelain tile was studied on industrial (1000 mm x 500 mm x 10 mm) and laboratorial (100 mm x 50 mm x 6 mm) scale. Industrial test pieces were fired at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…It can be observed that, approximately, from a temperature of 900 °C, the studied compositions began to show a negative deformation, i.e., concavity, owing to the beginning of the formation of a liquid phase from the fusion of clay minerals and the action of gravity [ 21 ]. Between 975 and 1025 °C, the increase in the deformation was interrupted by the formation of mullite at 1005 °C, which stabilised the structure, as shown in the DSC graph of the studied compositions in Figure 12 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be observed that, approximately, from a temperature of 900 °C, the studied compositions began to show a negative deformation, i.e., concavity, owing to the beginning of the formation of a liquid phase from the fusion of clay minerals and the action of gravity [ 21 ]. Between 975 and 1025 °C, the increase in the deformation was interrupted by the formation of mullite at 1005 °C, which stabilised the structure, as shown in the DSC graph of the studied compositions in Figure 12 .…”
Section: Resultsmentioning
confidence: 99%
“…The test consisted of an arrangement of a standardised specimen (3 mm × 5 mm × 80 mm) supported on two points. With warm-up, it was expected that this body would form an arrow shape, owing to the effect of gravity [ 21 ]. This test was performed on composition samples C0, C1, C2, and C3 in an optical fleximeter (Expert System Solutions, model Misura Flex ODLT, Modena, Italy) at a heating rate of 10 °C/min.…”
Section: Methodsmentioning
confidence: 99%